Palynology of Late Pleistocene varved clays from ice-dammed lakes at Lębork and Złocieniec (north-western Poland) – preliminary results - Gedl, Przemysław (Geologos, 2011)
Samples collected from Late Pleistocene varved clays of the Vistulian (Weichselian) glaciation exposed at Lębork and Złocieniec (Gardno and Pomeranian phases, respectively) yielded palynological contents that are related to the different lithologies composing the varves. The dark-coloured clay units contain very small amounts of palynological material. The lighter-coloured, much thicker coarser units yielded large amounts of organic particles consisting of predominantly palynodebris of terrestrial plants, sporomorphs and aquatic palynomorphs. The latter include fresh-water and marine phytoplankton. All particles were presumably washed out from the pre-Quaternary basement or from erratic material. This is indicated by the dinoﬂagellate-cyst assemblages, which represent Cretaceous and Palaeogene taxa. The large amounts of organic particles in the light-coloured layers indicate high-energy meltwaters streams, which washed them out, transported them and deposited them in ice-dammed lakes. The barren layers and those with lower amounts of organic particles were deposited during calm, presumably winter, periods, when the energy of the meltwater streams was much lower.